Contributions of Problem-Based Learning to the achievemente of meaningful learning in the teaching of Medicine. - Torres Paez, Fidel Fabian; Londoño, Jaime Alfonso (Spanish Journal of Medical Education, 2024)
In recent decades, medicine programs have been recognizing and implementing teaching strategies aimed at promoting critical, meaningful and open learning. Within them, Problem-Based Learning (PBL) is presented as an innovative strategy with a critical sense and self-training. Therefore, this study seeks to understand the contributions of the PBL teaching strategy to the achievement of meaningful learning in students of the medicine program at the University of Pamplona. A qualitative research design is chosen that follows the hermeneutic process to understand and interpret the experiences of the audiences around the use of PBL, which were addressed through semi-structured interviews with members of the Curriculum Committee, surveys of teachers through an electronic form, and focus groups with students. The data were analyzed, compared and interpreted in light of the bibliographical references and the results of the educative project of the program (PEP) documentary analysis. It is evident that there is a difference between the orientation of the PYP and the training proposal that teachers bring to the classroom, especially in relation to the use of didactic strategies, traditional ones such as the master class predominating. A lower use of active strategies is identified, among which PBL and the clinical case stand out, which are sometimes confused due to their problematizing nature. PBL is mainly used by teachers who have specialized training in pedagogy, but there is still a lack of greater structuring of the procedure. Motivation is configured as the main contribution of PBL to the achievement of significant learning.